Matilda - Dahl, Roald; Blake, Quentin; Juvenile Collection (Library of Congress) (New York : Puffin books, 1990)
Matilda applies her untapped mental powers to rid the school of the evil, child-hating headmistress, Miss Trunchbull, and restore her nice teacher, Miss Honey, to financial security.
Keywords: Schools -- Fiction; Humorous stories; Imprints 20th century 1988; Juvenile literature -- England -- London -- 1988.